Pentingnya Menjaga Kesehatan Mental bagi Mahasiswa untuk Mencegah Stigma Bunuh Diri : (Studi Pada Mahasiswa Universitas Nasional Pasim) - Suci Salsabila Oktaviani; Sangita Merliana Putri; Sri Mulyeni (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Mental health is an important factor in determining individual well-being. This study aims to describe students' views on mental health, the challenges they face, and their views on suicide stigma among students. This study applied a descriptive qualitative method using in-depth interview techniques with 7th semester psychology students using an open-ended question guide. The results showed that the main challenges faced by students include academic pressure such as piling up assignments, thesis work, difficult time management, and anxiety about an uncertain future. Friendly, professional and free counseling services, as well as holding seminars, workshops or trainings to raise student’s awareness about the importance of mental health, should be provided by campus.